Health Impact Assessment and City Council Policy: Identifying Opportunities to Address Local Social Determinants of Health & Place-Health Relationships, 10 Years Later - Ryan Petteway; Shannon Cosgrove (Indiana University-Purdue University Indianapolis, 2020)
Background: Health Impact Assessment (HIA) can be used to assess any type of policy/program related to social determinants (SDH).  However, local public health departments (LHDs) have been slow to adopt formal use of HIA in efforts to address local SDH, even with growing evidence linking SDH and place-health relationships. Ten years ago we completed a review of Baltimore City Council policies to advance this conversation within the LHD. Our goal here is to revisit this review and, again, outline a process by which LHDs can: a) monitor local policies in regard to SDH and b) identify opportunities for potential HIA use. Methods:  We reviewed all policies introduced into Baltimore City Council in calendar years 2008 and 2009. We reviewed each policy to identify those with potential health impacts. We then categorized these policies as: a) "explicitly health-related" or b) "related to SDH." We then tabulated the number and sub-types of these policies that were referred for LHD review. Results: We identified and reviewed 597 total policies. 89 policies (15%) were identified as "explicitly health-related," 34 (38%) of which were referred for LHD review. 208 policies (35%) were identified as "related to SDH," 13 (6%) of which were reviewed. Overall, 297 (50%) policies were identified as having potential health impacts, 47 (16%) of which were reviewed. Conclusion: This work represents a potentially replicable process to identify HIA opportunities, and potential launch point for health-in-all-policies efforts. In Baltimore, it facilitated dialogue with Baltimore City officials and led to the LHD's first HIA grant.